PENGEMBANGAN MEDIA GAMIFIKASI DO OR LEARN CARD DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN MOTIVASI BELAJAR IPS PESERTA DIDIK KELAS 8D SMP LABORATORIUM UM - Fariski, Aulia Isnaeni; Kurniawan, Bayu; Rahayu, Linda Zulkifa; Naufal, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning motivation is an important element in the success of the educational process, especially in learning Social Sciences (IPS) which is often considered monotonous and irrelevant by students. This study aims to develop and examine the effectiveness of Do or Learn Card learning media based on gamification integrated with the Culturally Responsive Teaching (CRT) approach to increase student learning motivation. This media is designed to provide a fun, participatory learning experience that is in accordance with the cultural background of students. The CRT approach is used to ensure that learning strategies value diversity and accommodate different learning styles. This study uses a development method based on the Design Thinking framework involving five stages: empathize, define, ideate, prototype, and test. The results of the study show that the use of this media has a significant impact on increasing student learning motivation, as indicated by the results of the pretest and posttest as well as positive responses from the satisfaction questionnaire.